Domestic tourists to Elmina Castle, Ghana: motivation, tourism impacts, place attachment, and satisfaction. Issue 12 (2nd December 2018) - Prayag, Girish; Suntikul, Wantanee; Agyeiwaah, Elizabeth
Abstract: Current research on dark tourism lacks an in-depth investigation of the relationships between the various psychological factors that influence tourist satisfaction. Using the cognitive-affective-behavior system, this paper evaluates a theoretical model that postulates relationships between four constructs, namely: motivation, perceptions of tourism impacts, place attachment, and satisfaction. The study extends the tourism literature on cultural sustainability by showing the psychological connections of domestic tourists to a dark heritage site, and the implications for perceptions of tourism impacts on this heritage. Based on a sample of 414 domestic tourists at a dark heritage site in Elmina, Ghana, PLS-SEM confirmed several inter-relationships among the four constructs. Motivation had a positive relationship with perceptions of positive and negative tourism impacts, suggesting that the tourists who were more motivated to visit the site for cultural/learning experiences were also more inclined to perceive both positive and negative tourism impacts. Implications for dark tourism and how heritage site management can influence tourists' perceptions of impacts are offered.